52 Needs assessment of end-of-life care in the emergency department. (14th March 2023) - Jacob, Faith; Hurlow, Adam; Deddick-Dyson, Stephanie; Fowler-Roughton, Grace; Ferguson, Aimee; Gillon, Suzie; Kite, Suzanne; Rees, Elizabeth
Abstract : Background: Improving end-of-life care (EOLC) in Emergency Departments (ED) is a top research priority for the Royal College of Emergency Medicine 1 Our hospital palliative care team created a Senior Clinical Nurse Specialist (CNS) role to facilitate quality improvement and address this priority. This project scoped the current workflow to identify needs and barriers to excellent EOLC in the ED. Methods: Retrospective review over ten months of patients' notes who received palliative care input, in ED. Baseline data was established, and processes identified, followed by eight weeks fieldwork. This included observation and consultation with ED and a Palliative CNS. Results: 150 patients received palliative care input whilst in ED. 33% (49) died within three days of admission to ED. Of these, 18% (9) died in ED and 59% (29) were admitted into hospital. Relationships have been built between Palliative Care and ED staff to enable a collaborative approach to driving improvement in these areas. From the fieldwork the points identified for improvement include: Rapid Discharge Pathway (RDP) being difficult to use; potentially patients at risk of dying in ED rather than preferred place of death; syringe driver training; access to equipment; lack of space for chairs, pillows and quietness to provide support at end-of-life for patients and families. ED team's knowledge on symptom management in EOLC is being explored. The process of patient flow in ED was identified, so patients 'to come in' (TCI) was acknowledged as a group to explore further for earlier palliative care interventions and support. Conclusions: Palliative care patients in ED are at risk of dying in ED or shortly after. Future work needed focusing on priorities identified eg streamlining the RDP, Training and renovation of ED environment. An in-reach service may help to identify a higher proportion of patients with palliative care needs. Reference: Smith J, Keating L, Flowerdew L, on behalf of the JLS EM PSP Steering Group, et al . An Emergency Medicine Research Priority Setting Partnership to establish the top 10 research priorities in Emergency Medicine Journal 2017;34 :454–456.